SAT0172 Economic outcomes, treatment patterns, and adverse events and reactions for patients prescribed infliximab or ct-p13 in the turkish population. (15th June 2017) - Phillips, K; Juday, T; Zhang, Q; Keshishian, A
Abstract : Background: CT-P13, a biosimilar drug product to infliximab, was approved and marketed in July 2014 in Turkey. There is little information on the costs, treatment discontinuation and adverse events and reactions between patients who switched from infliximab to CT-P13 and patients who continued infliximab. Objectives: The study objective was to evaluate health care costs, treatment discontinuation, and adverse events and reactions between patients who switched from infliximab to CT-P13 and patients who continued infliximab in the Turkish population. Methods: Adult patients with ≥1 claim for infliximab or CT-P13 were identified in a Turkish healthcare administrative database representing 80% of the Turkish population during the identification period (16 July 2014–31 Aug 2015). Patients were required to continuously use infliximab for ≥6 months with no hospitalizations. Eligible patients either continued on infliximab (index date: date of first infliximab prescription), or switched from infliximab to CT-P13 (index date: switch date). Patients were excluded if they had ≥1 condition with an indication for infliximab during the baseline period. Patients who switched to CT-P13 were 1:10 matched to patients who continued infliximab based on the length of infliximab use prior to the index date. Demographics and clinical characteristics were measured 12 months pre-index date. Generalized linear models were used to compare adjusted health care costs, Cox regression was used to evaluate the adjusted risk of discontinuation, and Poisson regression was used to evaluate the adjusted risk of adverse events and reactions. Results: The study included 1, 524 patients, of whom 1, 388 were continuous infliximab users and 136 switched to CT-P13. Ankylosing spondylitis and rheumatoid arthritis were the most common conditions indicated for infliximab and CT-P13; however, patients were much less likely to be switched to CT-P13 for other conditions. After adjusting for demographics and clinical characteristics, patients who switched to CT-P13 had higher outpatient ([Turkish lira] TL 269 vs TL 181; p=0.005), inpatient (TL 64 vs TL 29; p=0.313), and pharmacy costs (TL 1, 473 vs TL 1, 329; p=0.371), which resulted in significantly higher total health care costs (TL 2, 009 vs TL 1, 640; p=0.046) compared to patients who continued infliximab. Additionally, patients who switched to CT-P13 were more likely to discontinue treatment (13.2 vs 1.52 per 1000 person-years) compared to those who continued infliximab. Of patients who discontinued CT-P13, 79% switched back to infliximab. After adjusting for baseline characteristics, patients who switched to CT-P13 were significantly more likely to discontinue treatment compared to those who continued infliximab (HR=5.53; 95% CI: 4.01–7.63). There was no difference in the adjusted incidence rate ratio (IRR) between the cohorts for adverse events (IRR=0.67; 95% CI: 0.19–2.30) and reactions (IRR=0.84; 95% CI: 0.55–1.27). Conclusions: Patients who switched to CT-P13 had significantly higher health care costs and were also more likely to discontinue treatment compared to those who continued infliximab. However, there was no difference in the rate of adverse events and reactions. Disclosure of Interest: K. Phillips Consultant for: AbbVie Inc., T. Juday Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Q. Zhang Employee of: STATinMED Research, A. Keshishian Employee of: STATinMED Research